Impact of Educational Level on Performance on Auditory Processing Tests - Murphy, Cristina F. B.; Rabelo, Camila M.; Silagi, Marcela L.; Mansur, Letícia L.; Schochat, Eliane (Frontiers in Neuroscience, 2016)
Research has demonstrated that a higher level of education is associated with better performance on cognitive tests among middle-aged and elderly people. However, the effects of education on auditory processing skills have not yet been evaluated. Previous demonstrations of sensory-cognitive interactions in the aging process indicate the potential importance of this topic. Therefore, the primary purpose of this study was to investigate the performance of middle-aged and elderly people with different levels of formal education on auditory processing tests. A total of 177 adults with no evidence of cognitive, psychological or neurological conditions took part in the research. The participants completed a series of auditory assessments, including dichotic digit, frequency pattern and speech-in-noise tests. A working memory test was also performed to investigate the extent to which auditory processing and cognitive performance were associated. The results demonstrated positive but weak correlations between years of schooling and performance on all of the tests applied. The factor “years of schooling” was also one of the best predictors of frequency pattern and speech-in-noise test performance. Additionally, performance on the working memory, frequency pattern and dichotic digit tests was also correlated, suggesting that the influence of educational level on auditory processing performance might be associated with the cognitive demand of the auditory processing tests rather than auditory sensory aspects itself. Longitudinal research is required to investigate the causal relationship between educational level and auditory processing skills.